Factors related to rapid deceleration events among a large cohort of older drivers. (October 2019) - Eby, David W.; Molnar, Lisa J.; Zakrajsek, Jennifer S.; Ryan, Lindsay H.; Zanier, Nicole; St. Louis, Renée M.; Stanciu, Sergiu C.; LeBlanc, David; Bogard, Scott; Kostyniuk, Lidia P.; Smith, Jacqui; Yung, Raymond; et al.
Highlights: GPS data detected rapid deceleration events in a sample of older drivers Too few 0.75 g deceleration events were found for meaningful analysis. 0.35 g deceleration events were related to declining functional abilities. Several non ability-related factors were related to rapid deceleration events. 0.35 g deceleration events have limited value as a surrogate driving safety measure. Abstract: Studies over the past two decades have attempted to document and understand factors related to crashes involving older drivers to develop more effective countermeasures to reduce the frequency and severity of these crashes. Studies in which vehicle acceleration data can be recorded have begun to explore the relationship between rapid deceleration events (RDEs) and functional abilities among older drivers as a surrogate measure of unsafe driving. Recent naturalistic driving studies with older adults have found differing results using different thresholds to define an RDE. The present study examined the relationship among RDE rates, demographics, visual abilities, cognitive abilities, and driving comfort among a large cohort of older drivers, using two definitions of RDEs—longitudinal deceleration of 0.35 g or greater (RDE35) and longitudinal deceleration of 0.75 g or greater (RDE75). The study utilized objective driving, objective functioning, and reported driving comfort data from 2774 participants of the multi-site AAA Longitudinal Research on Aging Drivers (LongROAD) study. RDE rates for each threshold were calculated per 1000 miles driven. Multivariate regression models with backward elimination were developed to examine how outcome measures were related to RDE rates. Too few RDE75 events were found for meaningful analysis. RDE35 rates were significantly associated with several covariates. RDE35 rates were related to declining functional abilities, but many other factors also played a significant role in the rate of RDE35s among older drivers, diminishing the value of using RDE35 rates as a surrogate measure of driving safety. In addition, because the AAA LongROAD sample was relatively healthy and high functioning, other ability-related covariates may also be significantly related to RDE35s but the lack of variance in these measures in the current study prevented these effects from emerging.